Measurement of the masses and widths of the Sigma(++)(c) and Sigma(0)(c) charmed baryons - Artuso, M; Boulahouache, C; Bukin, K; Dambasuren, E; Mountain, R; Skwarnicki, T; Stone, S; Wang, J; Mahmood, A; Csorna, SE; Danko, I; Xu, Z; et al. (2002)
Using data recorded by the CLEO II and CLEO II.V detector configurations at CESR, we report new measurements of the masses of the ∑c++ and ∑c0 charmed baryons, and the first measurements of their intrinsic widths. We find M(∑c++)-M(Λc+) =167.4±0.1±0.2 MeV, Γ(∑c++)=2.3±0.2±0.3 MeV, and M(∑c0) -M(Λc+)=167.2±0.1±0.2 MeV, Γ(∑c0)=2.5±0.2±0.3 MeV, where the uncertainties are statistical and systematic, respectively.